Exercise interventions for depressive, manic, and anxiety symptoms in bipolar disorder: a systematic review and meta-analysis - Li, Xinmo; Liu, Feike; Ding, Feng; Ma, Xiaochen; Zhu, Yongguo (Frontiers in Psychiatry, 2025)
BackgroundTo evaluate the efficacy of exercise interventions on depressive, manic, and anxiety symptoms in patients with bipolar disorder (BD) through a systematic review and meta-analysis, and to explore the impact of different exercise parameters (session duration, frequency, etc.) on these symptoms.MethodsWe comprehensively searched Embase, Web of Science, PubMed, The Cochrane Library, Wan fang, Weipu Database(VIP), and China National Knowledge Infrastructure (CNKI) databases for randomized controlled trials (RCTs) published until May 2025. Included studies met the following criteria (1): participants aged ≥18 years with BD diagnosed according to Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) or International Classification of Diseases, 11th Revision (ICD-11) criteria (2); exercise as the primary intervention (3); control groups receiving standard rehabilitation treatment. Study quality was assessed using the Physiotherapy Evidence Database (PEDro) scale. Meta-analyses were performed using Stata 18.0, and evidence quality was evaluated with Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology.ResultsA total of 7 RCTs n=576 were included. Meta-analysis demonstrated that exercise significantly improved depressive symptoms (SMD =-0.63, 95%CI: -1.11 to -0.14, P=0.01) and anxiety symptoms (SMD =-0.70, 95%CI: -1.26 to -0.15, P<0.05) in BD patients, but showed no significant effect on manic symptoms (SMD =-0.23, 95%CI: -0.67 to 0.21, P>0.05). Subgroup analyses revealed that exercise protocols featuring session duration ≤1 hour/session (SMD= -0.86, P=0.02), frequency >5 sessions/week (SMD = -0.76, P<0.01), and intervention period ≤12 weeks (SMD = -0.79, P=0.02) produced more pronounced improvements in depressive symptoms. The GRADE approach rated the quality of evidence as low for all outcomes (depression, anxiety, mania), with downgrading factors including substantial heterogeneity, imprecision, and risk of bias.ConclusionCurrent low-quality evidence suggests that exercise may alleviate depressive and anxiety symptoms in BD patients (particularly with high-frequency, prolonged-duration, short-term protocols), while its effect on manic symptoms remains inconclusive. These findings should be interpreted cautiously due to methodological limitations of included studies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251041926.